Feasibility and efficacy of active remote monitoring of home ventilation in pediatrics. Issue 12 (18th August 2021) - Thomas, Alex; Langley, Ross; Pabary, Rishi
Abstract: Background: Non‐invasive positive airway pressure (PAP) therapy is used to treat children with sleep‐disordered breathing. Effective management requires good adherence. In response to the problem of reduced adherence over time, a pilot study using ventilators equipped with technology to remotely monitor home adherence was undertaken. Methods: From July 2019, children requiring PAP therapy consented for remote monitoring. Data collected included ventilator usage, apnea‐hypopnea index (AHI), and mask leak. Parents were contacted on Days 14, 42, and 90 post‐establishment. A proforma was used to assess parental understanding and ways to improve therapy adherence. A parental feedback questionnaire was completed on Day 90 of the study. Results: Median nightly PAP usage over 90‐day post‐establishment was 6.58 h (interquartile range: 2.47–8.62); 60% of patients met criteria for good adherence (>4 h for >70% of nights). There was a decrease in median nightly usage in Week 1 (6.92 h) versus Week 12 (6.15 h), p = 0.04. Mask leak was higher in Week 1 (17.7 L/min) versus Week 12 (14.7 L/min), p = 0.053. There was no significant difference in AHI between Week 1 (2.7/h) versus Week 12 (2.3/h), p = 0.75. 45% of questionnaire respondents felt active remote monitoring positively influenced PAP usage, whilst 84% reported overall satisfaction with PAP therapy. Conclusions: Remote monitoring technology has the potential to guide adjustments in PAP therapy, monitor and improve adherence in children, and reduce the burden of hospital‐based review. Preliminary work shows high approval from parents.